Vertical distribution of antibiotics and antibiotic resistance genes in a representative municipal solid waste landfill, China - Hong Li; Libo Qiu; Binhui Chen; Hua Wang; Hongyuan Liu; Yuyang Long; Lifang Hu; Chengran Fang (Ecotoxicology and Environmental Safety, 2022)
The vertical distribution of sulfonamides (SAs), tetracyclines (TCs), macrolides (MLs), and their related antibiotic resistance genes (ARGs) were comprehensively investigated and characterized in a representative municipal solid waste (MSW) landfill in China. The total concentrations of target antibiotics in the MSW landfill were SAs > TCs > MLs. The abundances of mexF (10.78 ± 0.65 log10copies/g) and sul genes (9.15 ± 0.54 log10copies/g) were relatively high, while the tet genes (7.19 ± 0.77 log10copies/g) were the lowest. Both the abundance of antibiotics and genes fluctuated with landfill depth, and the ARGs of the same antibiotics were consistent with depth change. Intl1 and sul genes (sul1, sul2) were tightly connected, and a close relationship also existed between tet genes (tetM, tetQ) and MLs resistance genes (ermB, mefA). High-throughput sequencing showed the dominant genera were Sporosarcina (38%) and Thiobacillus (17%) at sampling points A and C, while the microbial community varied with depth increase at point B were Brevundimonas (20%), Sporosarcina (20%), Pseudomonas (24%), Lysobacter (28%), and Thioalkalimicrobium (14%), respectively. Network analysis further visualized the relationship among antibiotics, genes, and microbial communities and the results indicated the non-random connection among them and the possible host of the target gene. Even at 12.0 m below the landfill surface, the pollution of antibiotics resistance was still serious, which posed difficulties for subsequent landfill remediation and pollution control.